2009
DOI: 10.1104/pp.109.138024
|View full text |Cite
|
Sign up to set email alerts
|

MERE1, a Low-Copy-Number Copia-Type Retroelement in Medicago truncatula Active during Tissue Culture    

Abstract: We have identified an active Medicago truncatula copia-like retroelement called Medicago RetroElement1-1 (MERE1-1) as an insertion in the symbiotic NSP2 gene. MERE1-1 belongs to a low-copy-number family in the sequenced Medicago genome. These copies are highly related, but only three of them have a complete coding region and polymorphism exists between the long terminal repeats of these different copies. This retroelement family is present in all M. truncatula ecotypes tested but also in other legume species l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 67 publications
0
31
0
2
Order By: Relevance
“…The Tnt1 insertion mutant lines were generated at the Noble Foundation (Tadege et al, 2008). The MERE1 insertion mutant line MS240 corresponds to a somaclonal variant obtained by regeneration of a T-DNA-tagged Medicago line (Scholte et al, 2002;Brocard et al, 2006;Rakocevic et al, 2009). For expression studies using the b-glucuronidase reporter gene, transgenic plants expressing a DNF2 promoter::gus fusion (pMB132 construct, see later) were generated by Agrobacterium tumefaciens strain EHA105 transformation of M. truncatula R108, as described in Cosson et al (2006).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The Tnt1 insertion mutant lines were generated at the Noble Foundation (Tadege et al, 2008). The MERE1 insertion mutant line MS240 corresponds to a somaclonal variant obtained by regeneration of a T-DNA-tagged Medicago line (Scholte et al, 2002;Brocard et al, 2006;Rakocevic et al, 2009). For expression studies using the b-glucuronidase reporter gene, transgenic plants expressing a DNF2 promoter::gus fusion (pMB132 construct, see later) were generated by Agrobacterium tumefaciens strain EHA105 transformation of M. truncatula R108, as described in Cosson et al (2006).…”
Section: Plant Materialsmentioning
confidence: 99%
“…LORE1 and LORE2 in L. japonicus are Ty3/ gypsy-like retroelements (Fukai et al, 2008) that have similar potential for isolating knockout mutants in this model to the use of Tnt1 in M. truncatula. Likewise, MERE1 in M. truncatula is a copia-like element found to transpose during tissue culture at a reduced frequency when compared to the heterologous Tnt1 (Rakocevic et al, 2009).…”
Section: Insertion Mutagenesismentioning
confidence: 99%
“…Further analysis showed that a Tnt1 retrotransposon was inserted in exons of LOL1 in lol1-1, lol1-2, and lol1-3. However, lol1-4 carried a native retrotransposon, Medicago RetroElement1 (Rakocevic et al, 2009) (Figure 3A). The expression of LOL1 was interrupted in all four lol1 alleles ( Figure 3C).…”
Section: Lol1 Encodes An Argonaute Proteinmentioning
confidence: 99%